The Waqf Mosque and Social Transformation Efforts at the Great Mosque of Imam Ulomo, Sampung, Ponorogo. - Huda, Miftahul; Humaidi, Muchtim; Syahruddin, Syahruddin (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract The Great Mosque of Imam Ulomo in Sampung, Ponorogo, is a waqf mosque with significant potential for social transformation. This article examines the role of waqf mosques in productive-based management to foster socio-economic transformation in rural areas. Using the Asset-Based Community Development (ABCD) approach, the study employs participatory methods, including focus group discussions (FGD), interviews, and document analysis. The findings highlight that strengthening nazhir capacity and optimizing waqf assets, such as agricultural land management and fish farming, significantly contribute to empowering the surrounding community. The implementation of a productive waqf management paradigm has successfully established professional governance, enhanced accountability, and expanded socio-economic impact. These findings recommend sustainable programs to support mosque-based rural transformation initiatives.